2010
DOI: 10.1080/03055690903424816
|View full text |Cite
|
Sign up to set email alerts
|

Communities of practice in inclusive education

Abstract: The data in this paper represent the experiences and perspectives of parents and teachers who worked as communities of practice, designing support plans for the inclusion of three students with intellectual disabilities in general education classrooms. Their reflections, obtained through interviews and questionnaires, show how they constructed relevant knowledge to support these children with special educational needs in their class. The findings show the potential benefits of partnerships and local knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…As teacher attitudes are highly influential on the support and inclusion of students with special needs in regular classrooms (Macfarlane, 2007;Sze, 2009), teacher educators must play active roles in developing inclusive attitudes among pre-service classroom teachers. The values instilled in classroom teachers during their preservice education are critical to their development of classroom practices that support the inclusion of children with diverse learning needs (Mortier, Hunt, Leroy, van de Putte, & van Hove, 2010). Mortier et al (2010) research implies the need for teacher educators to support preservice teachers" development of inclusive attitudes by emphasizing the need for partnership between teachers and parents within local contexts.…”
Section: Education Context In Cameroonmentioning
confidence: 99%
See 1 more Smart Citation
“…As teacher attitudes are highly influential on the support and inclusion of students with special needs in regular classrooms (Macfarlane, 2007;Sze, 2009), teacher educators must play active roles in developing inclusive attitudes among pre-service classroom teachers. The values instilled in classroom teachers during their preservice education are critical to their development of classroom practices that support the inclusion of children with diverse learning needs (Mortier, Hunt, Leroy, van de Putte, & van Hove, 2010). Mortier et al (2010) research implies the need for teacher educators to support preservice teachers" development of inclusive attitudes by emphasizing the need for partnership between teachers and parents within local contexts.…”
Section: Education Context In Cameroonmentioning
confidence: 99%
“…The values instilled in classroom teachers during their preservice education are critical to their development of classroom practices that support the inclusion of children with diverse learning needs (Mortier, Hunt, Leroy, van de Putte, & van Hove, 2010). Mortier et al (2010) research implies the need for teacher educators to support preservice teachers" development of inclusive attitudes by emphasizing the need for partnership between teachers and parents within local contexts. In the field of preservice teacher education, there is no published research on inclusive education in Cameroon.…”
Section: Education Context In Cameroonmentioning
confidence: 99%
“…These interventions should consider conversational topics that are context-appropriate and similar to those of general education students. Mortier et al (2010) suggested that the shared expertise of teachers, specialists, and parents working as a community can be empowering and helpful for inclusion. In that study, the communities met once a month and discussed a child's school experience and what they could do to support it.…”
Section: Inclusionmentioning
confidence: 99%
“…Despite researchers' arguments, teachers have stated that they do not feel confident offering fully inclusive classrooms if they lack specialized skills and knowledge (Florian & Linklater, 2010;Kamens et al, 2003;Mortier et al, 2010), and they feel anxious when teaching diverse students (Avramidis & Norwich, 2002;Blecker & Boakes, 2010). There are no accurate statistics of inclusive education, but it seems that full inclusion of students with intellectual disabilities is not common in countries that do not legally prescribe inclusion as the only option (Anderson et al, 2011;U.S.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation